IOFI recommended practice for the use of predicted relative‐response factors for the rapid quantification of volatile flavouring compounds by GC‐FID. (2nd February 2016) - Cachet, T.; Brevard, H.; Chaintreau, A.; Demyttenaere, J.; French, L.; Gassenmeier, K.; Joulain, D.; Koenig, T.; Leijs, H.; Liddle, P.; Loesing, G.; Marchant, M.; et al.
Abstract: This recommended practice enables the quantification of volatile compounds in flavourings to be made by gas chromatography with flame‐ionization detection, without having authentic compounds available, and also in many cases it can avoid time‐consuming calibration procedures. The relative‐response factors (RRF) can be predicted from the molecular formula of the compound, and this approach can be applied to compounds containing the atoms C, H, O, N, S, F, Cl, Br, I, and Si, providing that the molecular formula and number of benzene rings in the analytes are known. The purity of chemically‐defined flavouring substances or chromatographic standards can also be estimated using these predicted RRF, and this procedure can also be used to quantify (poly)hydroxylated compounds, after their derivatization into trimethylsilyl ethers or esters. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This recommended practice enables the quantification of volatile compounds in flavourings to be made by gas chromatography with flame‐ionization detection, without having authentic compounds available, and also in many cases it can avoid time‐consuming calibration procedures. The relative‐response factors can be predicted from the molecular formula of the compound, and can be applied to compounds containing the atoms C, H, O, N, S, F, Cl, Br, I, and Si, providing that the molecular formula and number of benzene rings in the analytes are known.